2014
DOI: 10.1371/journal.pone.0113344
|View full text |Cite
|
Sign up to set email alerts
|

Different Regions of the Newcastle Disease Virus Fusion Protein Modulate Pathogenicity

Abstract: Newcastle disease virus (NDV), also designated as Avian paramyxovirus type 1 (APMV-1), is the causative agent of a notifiable disease of poultry but it exhibits different pathogenicity dependent on the virus strain. The molecular basis for this variability is not fully understood. The efficiency of activation of the fusion protein (F) is determined by presence or absence of a polybasic amino acid sequence at an internal proteolytic cleavage site which is a major determinant of NDV virulence. However, other det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Recently, [23] observed an increase in virus virulence following deletion of N glycans from the heptad repeats of the NDV F protein. Furthermore, [24] showed a dramatic increase in NDV virulence when the cytoplasmic tail from a mesogenic strain was used to replace its counterparts in another lentogenic strain, suggesting the possible role of the F protein's cytoplasmic domain in determining the virulence of NDV. The HN protein is also believed to be a determinant of NDV virulence.…”
Section: Virulence Determinantsmentioning
confidence: 99%
“…Recently, [23] observed an increase in virus virulence following deletion of N glycans from the heptad repeats of the NDV F protein. Furthermore, [24] showed a dramatic increase in NDV virulence when the cytoplasmic tail from a mesogenic strain was used to replace its counterparts in another lentogenic strain, suggesting the possible role of the F protein's cytoplasmic domain in determining the virulence of NDV. The HN protein is also believed to be a determinant of NDV virulence.…”
Section: Virulence Determinantsmentioning
confidence: 99%
“…The HN protein of NDV plays an important role in viral infection because it possesses the receptor recognition activity, while viral infection is initiated by attachment of the virion to the sialic acid-containing receptors on the surface of the target cell. HN protein can also promote fusion activity via its interaction with the F protein and act as an NA by removing sialic acid from progeny virus particles to prevent viral self-aggregation, aiding virus infection ( Mirza et al, 1994 ; Huang et al, 2004 ; Melanson and Iorio, 2004 ; Heiden et al, 2014 ; Liu B. et al, 2015 ; Jin et al, 2016 ). Our results showed that HN proteins of the five selected NDV strains in this study had markedly different HAd, NA and fusogenic promotion activities at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the F protein mediates virus entry and fusion with the cell membrane for most avian paramyxoviruses type 9 (APMV-9) strains. Recent reports show that the F protein cleavage site sequence is not a major determinant of pathogenicity and virulence of APMV-7 in chickens [171], and other regions of the F protein could modulate virus virulence [172]. In influenza A virus, the cleavage site of HA is Rx[RK]RÓGLF in highly pathogenic avian influenza virus H5N1, while RxxRÓ, RxRRÓ, and KKKRÓ are also reported [111].…”
Section: Cleavage Site Motifmentioning
confidence: 99%